(untitled) (Applied Biological Research, 2023)
Caligids are one of the most frequently occurring copepod parasites of marine and brackish water fishes, which cause a great havoc to the mariculture. There isahugebiodiversityof marine fishes andtheirparasites in the Bay of Bengal. The present study was aimed to unravel the copepod parasite diversity in marine thread fin fishes of Visakhapatnam coast, Andhra Pradesh (India). A new species of Caligus Muller, 1785 was obtained from the gills of 77 Polydactylus plebeius (Broussonet) and 55 Leptomelanosoma indicum (Shaw) of Visakhapatnam coast, India, fixed in 10% formalin and cleared ia few drops of lactic acid for 12-24 h before identification. The species was characterized by having urn-shaped genital segment, large lunules, indistinctly two-segmented abdomen, converging tines of sternal fork, presence of three rows of teeth on the middle segment of endopod of 2nd leg, three segmented 4th leg and absence of ventral setae on distal segment of 1st leg. Based on above differences in vital diagnostic features and their occurrence in polynemid fishes, they are regarded as new species of Caligus and named as Caligus polynemi n. sp. Further monitoring surveys may enable sustainable marine fish farming by exploring unknown species from different geographical locations and develop various pest management anconservation strategies against them to safeguard marine life.